Stathmin is expressed by the proliferating hepatocytes during liver regeneration. Issue 2 (April 1995) - Rowlands, D C; Harrison, R F; Jones, N A; Williams, A; Hubscher, S G; Brown, G
Abstract : Aim —To determine the liver cell populations that express the phylogenetically conserved cytosolic protein stathmin during liver regeneration. Methods —Double immunostaining for stathmin and the Ki67 antigen was performed on sections of formaldehyde fixed, paraffin wax embedded tissues from 31 liver specimens. These included a variety of disease conditions characterised by some degree of hepatocyte regeneration. Quantitative western blot analysis was performed on 22 of these specimens. Results —Variable amounts of stathmin protein were detected by western blotting in all of the specimens examined. Stathmin was not detected in three cases of histologically normal liver. On immunostaining, stathmin was demonstrated in a proportion of hepatocytes as well as lymphoid inflammatory cells and other tissue elements. In all cases most of these stathmin positive cells showed nuclear positivity for the Ki67 antigen. Conclusions —Stathmin is expressed by proliferating hepatocytes but not by resting hepatocytes. Thus, it is likely that the protein has a function important to cell proliferation as opposed to cell differentiation.